THE APOPTOSIS INDUCTION OF Zingiber oficinale ETHANOLIC EXTRACT-Treated HeLa (HUMAN CERVICAL CANCER) CELLS AND ACTIVE COMPOUND PROFILING USING GAS CHROMATOGRAPHY/MASS SPECTROMETRY - Laela Hayu Nurani; Siti Rofida; Dwi Utami; Citra Ariani Edityaningrum; Any Guntarti (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Cervical cancer accounts for the highest percentage of cancer-related deaths in Indonesia, accounting for nearly 60% of all cancer cases. Therefore, research into the anticancer mechanisms needs to be conducted. The ethanolic extract of Zingiber officinale (EEZO) contains zingiberene, a chemical known for its anticancer activity. Understanding the mechanism underlying the apoptosis-inducing effects is crucial. This study aimed to elucidate the apoptotic pathway and analyze the gas chromatography/mass spectrometry (GC/MS) profile of EEZO cells. The research commenced with the maceration of Zingiber officinale rhizomes using 75% ethanol to obtain EEZO. Apoptosis assays were conducted on both a negative control group and an EEZO-treated group of HeLa cells (cervical cancer cells). The apoptotic mechanism was evaluated using forward scattered light-side scattered light (FSC-SSC), fluorescein isothiocyanate (FTIC), and phycoerythrin (PE) flow cytometry. Apoptotic results were analyzed by comparing the control and EEZO samples, which revealed the number of viable cells, apoptotic cells, and cells in the sub-G1 phase. The major constituent of EEZO, which is expected to be a potent apoptosis inducer, was detected using GC/MS. The FSC-SSC results indicated a lower number of viable cells in the EEZO-exposed group than in the control group. FTIC results demonstrated that EEZO significantly increased apoptotic cell death, increasing from 68 to 1537 cells. PE flow cytometry revealed an elevated sub-G1 cell population, indicating the induction of apoptosis by EEZO. GC/MS analysis revealed five dominant components in EEZO, which had the potential to induce apoptosis: L-borneol, zingiberene, farnesol, beta-sesquiphellandrene, and alpha-curcumene ...